SAPrIm, a semi-automated protocol for mid-throughput immunopeptidomics - Lim Kam Sian, Terry C. C.; Goncalves, Gabriel; Steele, Joel R.; Shamekhi, Tima; Bramberger, Liesl; Jin, Dongbin; Shahbazy, Mohammad; Purcell, Anthony W.; Ramarathinam, Sri; Stoychev, Stoyan; Faridi, Pouya (Frontiers in Immunology, 2023)
Human leukocyte antigen (HLA) molecules play a crucial role in directing adaptive immune responses based on the nature of their peptide ligands, collectively coined the immunopeptidome. As such, the study of HLA molecules has been of major interest in the development of cancer immunotherapies such as vaccines and T-cell therapies. Hence, a comprehensive understanding and profiling of the immunopeptidome is required to foster the growth of these personalised solutions. We herein describe SAPrIm, an Immunopeptidomics tool for the Mid-Throughput era. This is a semi-automated workflow involving the KingFisher platform to isolate immunopeptidomes using anti-HLA antibodies coupled to a hyper-porous magnetic protein A microbead, a variable window data independent acquisition (DIA) method and the ability to run up to 12 samples in parallel. Using this workflow, we were able to concordantly identify and quantify ~400 - 13000 unique peptides from 5e5 - 5e7 cells, respectively. Overall, we propose that the application of this workflow will be crucial for the future of immunopeptidome profiling, especially for mid-size cohorts and comparative immunopeptidomics studies.